Normative substantiation of production, quality control and safety of medicinal products on the basis of nanomaterials - Bilous Svіtlana; Kalyniuk, Timofiy (ScienceRise: Pharmaceutical Science, 2017)
Aim. The analysis of Ukrainian normative documents concerning remedies based on nanomaterials and the study of international experience on their development, quality control and safety. Methods. Methods of information retrieval and literature data analysis have been used. Results. The analysis of the State Pharmacopoeia of Ukraine, the orders of the Ministry of Health of Ukraine and other Ukrainian normative documents concerning medicines based on nanomaterials, as well as the EU legal framework on nanotechnologies and nanomaterials has been conducted. The necessity of development and approval in Ukraine of the regulatory and legal framework for medicines based on nanomaterials has been substantiated. Conclusion. The question of expediency of working out the normative and legal base for creation of medicines on the basis of nanomaterials in Ukraine is uncontested. The first steps in this direction have already been taken, but the question is still far from the solution. The lack of regulatory requirements for production, quality control and safety of medicines with nanomaterials complicates their development and makes it impossible to introduce into production